A Highly Efficient Method for the Bromination of Alkenes, Alkynes and Ketones Using Dimethyl Sulfoxide and Oxalyl Bromide - Ding, Rui; Li, Jiaqi; Jiao, Wenyi; Han, Mengru; Liu, Yongguo; Tian, Hongyu; Sun, Baoguo (Synthesis, 2018)
The pairing of DMSO and oxalyl bromide is reported as a highly efficient brominating reagent for various alkenes, alkynes and ketones. This bromination approach demonstrates remarkable advantages, such as mild conditions, low cost, short reaction times, provides excellent yields in most cases and represents a very attractive alternative for the preparation of dibromides and α-bromoketones.
Keywords: bromination; dimethyl sulfoxide; oxalyl bromide; alkenes; alkynes; ketones; bromodimethylsulfonium salt